Los cuentos infantiles y el pensamiento lógico – matemático en los niños de 4 a 5 años de la Unidad Educativa Lauro Damerval Ayora de la cuidad de Loja, periodo 2023 – 2024 - Ramírez Tacuri, Amparo Elizabeth (2024)
A community commitment is required to develop skills that foster reasoning, problem solving, and mathematical understanding in children by making the logical-mathematical area an exclusive learning area through playful activities that awaken interest through active strategies. The objective is to assist children in understanding and acquiring abstract ideas in a structured and coherent manner, as well as to assist them in understanding and acquiring abstract ideas, preparing them to face academic and daily challenges in a logical manner. The purpose of this study was to determine whether children's stories contribute to the improvement of logical-mathematical thinking in children from 4 to 5 years old at the Lauro Damerval Ayora Educational Unit in Loja, during the period 2023 to 2024. It was executed with a non-experimental design, mixed approach and descriptive scope, also the following methods were used: inductive - deductive and analytical - synthetic, with direct observation technique. In the same way, the TEMT test was used, which was applied to twenty-two children, obtaining as a result that most of the children are located in low and very low level having difficulties in: classification, comparison, seriation, one-to-one correspondence and verbal counting, with this, several studies that verified the importance of children's stories for the acquisition of mathematics in children were investigated. In addition, an activity guide titled Aprendamos divirtiéndonos con los cuentos matemágicos (Let's learn and have fun with mathematical stories)" was designed, comprising twenty-five activities based on a variety of stories that contribute to strengthening logical-mathematical thinking, stimulating the development of various areas, specifically in the area of mathematics, by implementing fun and active dynamics that encourage each child's participation. Key words: Learning, mathematics in pre-school, narratives, notions, reasoning, short stories.